Multivariate Analysis of Attitudes, Knowledge and Use of ICT in Students Involved in Virtual Research Seedbeds - Magda Alejandra Martinez-Daza; Alfredo Guzmán Rincón; Jader Alexis Castaño Rico; Nuria Segovia-García; Harvey Yesid Montilla Buitrago (MDPI AG, 2021)
The incorporation of information and communication technologies (ICTs) in higher education has been carried out in a transversal manner within the curriculum, and the processes of formative research in both face-to-face and virtual programmes are not an exception to this process. In this context, it is recognised that students' perceptions of the inclusion of technologies in the classroom can influence their teaching and learning process; however, they have not been widely addressed in multiple settings including research seedbeds. Thus, this paper aims to identify such perceptions represented in the attitudes, knowledge and uses of ICTs in students ascribed to the research seedbed in a virtual business administration programme of an Institution of Higher Education located in Colombia. For its fulfillment, the ACUTIC scale was applied to a sample of 65 students in order to identify these perceptions through a hierarchical cluster analysis, a single factor analysis of variance (ANOVA) test, a post hoc Tukey method and a factor analysis. The main result is that attitudes, knowledge and use of ICTs are varied and they can be represented in three clusters. In general, the attitude towards the incorporation of technologies in the research seedbed is positive; however, there is a gap in terms of knowledge and use, especially of those tools oriented to the disciplinary field and research.